Studi Komparatif Self-Compassion pada Generasi Milenial dan Generasi Z - Andini Nur Hasanah; Dita Mediasari (Dinasti Research, 2024)
This study aims to determine whether there is a significant difference between Millennials and Generation Z during the quarter-life crisis phase living in Bandung. The research uses the Self-compassion theory proposed by Neff (2003). Self-compassion, which includes the aspects of self-kindness, common humanity, and mindfulness, plays a crucial role in helping individuals cope with life pressures, failures, and identity crises. Both generations face different challenges in terms of education, career, and social relationships, which potentially impact their psychological well-being. Using a quantitative approach, this research involves interviews with individuals from both generations to analyze differences in Self-compassion levels when facing various quarter-life crisis issues. The measurement tool used is the standardized Self-compassion Scale (SCS), consisting of 26 items translated by Sugianto et al. (2020). The hypothesis was tested using an Independent T-test, and the results showed a significance value of p < 0.001. The sub-dimensions showed self-kindness p = 0.045, common humanity p = 0.002, and mindfulness p = 0.003, indicating a significant difference between Millennials and Generation Z during the quarter-life crisis phase in Bandung City.